2023
DOI: 10.3389/frvir.2023.1019080
|View full text |Cite
|
Sign up to set email alerts
|

TwinXR: Method for using digital twin descriptions in industrial eXtended reality applications

Abstract: Digital twins (DTs) and eXtended Reality (XR) are two core technological enablers for engineering in the Metaverse that can accelerate the human-centric Industry 5.0 transformation. The digital twin technology provides a digital representation of a physical asset with data linkages for inspection, monitoring, and prediction of complex processes or systems, while eXtended reality offers real-and-virtual combined environments for human users to interact with machines. However, the synergies between digital twins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…This layer enables real-time visual monitoring of the system's operational status, thus serving as a critical touchpoint for users. The Visualization Layer also incorporates advanced immersive technologies like VR, AR, and Hybrid Reality, collectively known as Extended Reality (XR) [117,118]. XR technologies offer a seamless integration between the physical and virtual worlds, creating a visually compelling, immersive, interactive experience for users.…”
Section: Visualization Layermentioning
confidence: 99%
“…This layer enables real-time visual monitoring of the system's operational status, thus serving as a critical touchpoint for users. The Visualization Layer also incorporates advanced immersive technologies like VR, AR, and Hybrid Reality, collectively known as Extended Reality (XR) [117,118]. XR technologies offer a seamless integration between the physical and virtual worlds, creating a visually compelling, immersive, interactive experience for users.…”
Section: Visualization Layermentioning
confidence: 99%
“…The use of VR and extended reality (XR, representing all technologies that merge the physical and virtual worlds) has been widely investigated across various sectors, notably in Industry 5.0, Architecture, Engineering, and Construction (AEC), and education. Tu et al (2023) emphasized the role of digital twins (DTs) and XR in accelerating the human-centric Industry 5.0 transformation, highlighting their ability to provide digital representations of physical assets and offer interactive environments for humans and machines [10]. Alizadehsalehi et al (2020) demonstrated the value of XR in simulating multidimensional digital models of construction projects [11], while Bellalouna (2019) discussed the potential of VR for cognitive design-review and failure modes and effects analysis (FMEA) in industrial engineering [12].…”
Section: Literature Review 21 Development Of Vr Devices and Softwarementioning
confidence: 99%
“…Finally, mixed or "hybrid" reality is defined as the mixing of physical and digital reality (Pimentel and Teixeira, 1993;Wu et al, 2013;Di Tore et al, 2020). Thanks to the integrated use of emerging technologies (digital twins, block chain, holography, IoT) (Center for Journalism Studies of Tsinghua University, 2021; Kang, 2021;Lv et al, 2022;Park and Kim, 2022;Prieto et al, 2022), the metaverse is nowadays assumed as extended reality (XR), that effectively integrates and overcome the simple sum of augmented, mixed and virtual reality technologies (Park and Kim, 2022;Tu et al, 2023 -see Figure 1). Specifically, in the metaverse interaction performance, evaluation and user emotional responses would be made more vivid by an interaction-feedback system guided and mediated by artificial intelligence that analyzes numerous data in real time (Hennig-Thurau et al, 2023) -see Figure 2.…”
Section: Introduction 1meanings Of Metaversementioning
confidence: 99%